Child Rights Reflected In Helen Hooven Santmyer's The Fierce Dispute Novel (1929): A Sociological Perscpective - Wulandari, Vita, Dr. M Thoyibi, M.S, Nur Hidayat, M.Pd (2014)
This study is about Child Rights. The problem of this study is on how child rights is expressed in The Fierce Dispute novel. The objectives of this study are to identify the characteristic of child rights in The Fierce Dispute novel, to describe child rights in The Fierce Dispute novel, and to reveal the necessity for Helen Hooven Santmyer to address child rights. The object of the study is The Fierce Dispute novel by Helen Hooven Santmyer. The study uses sociological perspective. This study belongs to qualitative research. In this method, there are two types of data sources, namely primary and secondary data source. The primary data source is the novel and the secondary data is other material related to the study. Both data are collected through library research and analyzed by descriptive analysis. The result of the study shows the following conclusions. First, based on the structural analysis it is clear that in The Fierce Dispute novel, Helen Hooven Santmyer delivers message that every child has the rights for social and life. Second, based on the sociological analysis, it is apparent that there is a strong relation between this novel and the social reality in American in early twentieth century.